2008
DOI: 10.1242/dev.022020
|View full text |Cite
|
Sign up to set email alerts
|

Localised axial progenitor cell populations in the avian tail bud are not committed to a posterior Hox identity

Abstract: The outgrowth of the vertebrate tail is thought to involve the proliferation of regionalised stem/progenitor cell populations formed during gastrulation. To follow these populations over extended periods, we used cells from GFP-positive transgenic chick embryos as a source for donor tissue in grafting experiments. We determined that resident progenitor cell populations are localised in the chicken tail bud. One population, which is located in the chordoneural hinge (CNH), contributes descendants to the paraxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
210
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(227 citation statements)
references
References 62 publications
5
210
0
Order By: Relevance
“…We propose that this zone shapes both the infundibulum and, potentially, the overlying hypothalamus, and that it can contribute cells to the infundibulum over an extended period. Intriguingly, other studies have shown that there is a second proliferative zone at the most caudal region of the forming neural tube, in which FGF signalling maintains cells in a proliferative, undifferentiated state (Diez del Corral et al, 2003;Delfino-Machin et al, 2005;McGrew et al, 2008). The two ends of the neural tube therefore share the ability to promote FGF signalling and establish proliferative zones.…”
Section: Fgf Signalling Governs Proliferating Sox3mentioning
confidence: 95%
“…We propose that this zone shapes both the infundibulum and, potentially, the overlying hypothalamus, and that it can contribute cells to the infundibulum over an extended period. Intriguingly, other studies have shown that there is a second proliferative zone at the most caudal region of the forming neural tube, in which FGF signalling maintains cells in a proliferative, undifferentiated state (Diez del Corral et al, 2003;Delfino-Machin et al, 2005;McGrew et al, 2008). The two ends of the neural tube therefore share the ability to promote FGF signalling and establish proliferative zones.…”
Section: Fgf Signalling Governs Proliferating Sox3mentioning
confidence: 95%
“…Fertilised green fluorescent protein transgenic (GFP-tg) eggs (McGrew et al, 2008) and wild-type eggs (Henry Stewart, UK) were incubated at 38°C for 3 to 6 days before windowing with sharp surgical scissors. A number of embryos at embryonic day (E)4-6 were removed from eggs and neural tubes dissected in Tyrode's solution.…”
Section: In Vitro and In Ovo Manipulationsmentioning
confidence: 99%
“…transgenic non-polydactylous Roslin Green embryos that express GFP ubiquitously (McGrew et al, 2008) and Slk embryos. We replaced the anterior half of the Slk leg bud with an equivalent half from a Roslin Green leg bud at stage 20HH and examined (Towers et al, 2008) in which posterior Shh signalling specifies digit number through growth across the anteroposterior axis and digit identity through a morphogen gradient across this field.…”
Section: Developmental Dynamicsmentioning
confidence: 99%